A fuzzy inference approach to analysis of LPV-200 procedures influence on air traffic safety. (September 2019) - Kaleta, Wojciech; Skorupski, Jacek
Highlights: Localizer Performance Vertical Guidance (LPV-200) approach procedures were examined. Controlled Flight Into Terrain (PoC) probability was determined by fuzzy inference. Experiments were carried out for airports with different navigational equipment. LPV-200 procedures allow the reduction of PoC for poorly equipped airports. In case of ILS failure, LPV-200 procedures allow maintaining the PoC at low level. Abstract: Introducing new technical and organizational solutions in air transport requires demonstrating that the level of safety will not be reduced. The LPV-200 (Localizer Performance with Vertical Guidance) approach for landing procedures represent a great opportunity for development of small, poorly equipped airports, as they permit precise landing without costly investment in the ILS (Instrument Landing System). The aim of this paper is to assess the effects of the introduction of LPV-200 procedures for air traffic safety which was determined by the probability of a CFIT (Controlled Flight Into Terrain) accident – PoC. Factors affecting PoC are of a diverse nature, some of which are subjective and cannot be expressed precisely. Therefore, PoC assessment uses fuzzy logic methods, and more specifically hierarchical fuzzy inference systems, with a knowledge base obtained from experts. As a result of simulation experiments, PoC was determined for airports with various levels of navigational equipment. It was also found that the introduction of LPV-200 procedures allows the reduction of PoC, with the highest effect being achieved for the least equipped airports. Also, in the event of failure of the main approach assistance system ILS, the use of LPV-200 procedures allows maintaining PoC at the same or close to the basic value level. The results of our research indicate that the introduction of LPV-200 procedures is clearly positive for the commercial use of small, less equipped aerodromes. We have shown that thanks to employing LPV-200 procedures it is possible to keep the PoC at a level similar to typical commercial airports.